2010
DOI: 10.1186/1471-2288-10-70
|View full text |Cite
|
Sign up to set email alerts
|

Automatic de-identification of textual documents in the electronic health record: a review of recent research

Abstract: BackgroundIn the United States, the Health Insurance Portability and Accountability Act (HIPAA) protects the confidentiality of patient data and requires the informed consent of the patient and approval of the Internal Review Board to use data for research purposes, but these requirements can be waived if data is de-identified. For clinical data to be considered de-identified, the HIPAA "Safe Harbor" technique requires 18 data elements (called PHI: Protected Health Information) to be removed. The de-identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
198
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(209 citation statements)
references
References 15 publications
1
198
0
1
Order By: Relevance
“…The majority of patients were in favor of data sharing among researchers, especially within the field of AD research, although support for the sharing of personal information decreased with a higher risk of re-identifying the data [47][48][49][50][51][52][53][54]. Trinidad and colleagues [55] also found that both current and prospective research participants are generally supportive of the sharing of non-identifiable data among researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients were in favor of data sharing among researchers, especially within the field of AD research, although support for the sharing of personal information decreased with a higher risk of re-identifying the data [47][48][49][50][51][52][53][54]. Trinidad and colleagues [55] also found that both current and prospective research participants are generally supportive of the sharing of non-identifiable data among researchers.…”
Section: Discussionmentioning
confidence: 99%
“…An overview of approaches to PHI de-identification is provided by Meystre et al [8]. From their analysis, they concluded that methods based on linguistic resources, such as dictionaries, tend to perform better with rarely mentioned PHIs.…”
Section: De-identificationmentioning
confidence: 99%
“…Later the need to sanitize the unstructured documents had come into notice. This need is revealed in initiatives from DARPA [11] or the Consortium for Healthcare Informatics Research (CHIR) [12] which aim at building new methods and tools for declassification of confidential documents. In the structured documents the structure itself provides the key to identify sensitive terms.…”
Section: Related Workmentioning
confidence: 99%